Effect of biphosphate salt on dipalmitoylphosphatidylcholine bilayer deformation by Tat polypeptide. Issue 8 (27th May 2022) - Patra, Piya; Banerjee, Raja; Chakrabarti, Jaydeb
Abstract: Translocation of positively charged cell penetrating peptides (CPP) through cell membrane is important in drug delivery. Here we report all‐atom molecular dynamics simulations to investigate how a biphosphate salt in a solvent affects the interaction of a CPP, HIV‐1 Tat peptide with model dipalmitoylphosphatidylcholine (DPPC) lipid bilayer. Tat peptide has a large number of basic arginines and a couple of polar glutamines. We observe that in absence of salt, the basic residues of the polypeptide get localized in the vicinity of the membrane without altering the bilayer properties much; polypeptide induce local thinning of the bilayer membrane at the area of localization. In presence of biphosphate salt, the basic residues, dressed by the biphosphate ions, are repelled by the phosphate head groups of the lipid molecules. However, polar glutamine prefers to stay in the vicinity of the bilayer. This leads to larger local bilayer thickness at the contact point by the polar residue and non‐uniform bilayer thickness profile. The thickness deformation of bilayer structure disappears upon mutating the polar residue, suggesting importance of the polar residue in bilayer deformation. Our studies point to control bilayer deformation by appropriate peptide sequence and solvent conditions. Abstract :